Manajemen Pendidikan Islam dalam Pengembangan Lembaga Pendidikan Islam - Suriadi Suriadi (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2019)
This article examines the management of Islamic education, in developing Islamic educational institutions. Educational management is management that is applied in the development of education. Educational management is more general in nature for all educational activities in general and educational institutions in particular, while management of Islamic education more specifically refers to management applied in the development of Islamic educational institutions. In a sense, how to use and manage the resources of Islamic educational institutions effectively to achieve the goals of development, progress and quality of the process and results of Islamic education itself. Certainly aspects of managers and leaders who are Islamic or who are illuminated and imbued with Islamic teachings and values, must be attached to the management of Islamic education. That the management of Islamic education is a process (planning, organizing, actuating, and controlling) of the Islamic use of all existing potentials (human or non-human, self and others) in totality in educational activities (efforts, institutions, and products) Islam, starting from the intention to Islamic and to achieve an Islamic goal. Management of Islamic education and become a basic belief to influence the effectiveness and productivity of work in the Islamic education environment and the achievement of objectives. The method used in this study is the study literature by analyzing various sources. The results of this study show that the organization of Islamic education is all resources to optimize the ability of each individual to realize cooperation in achieving the objectives of Islamic education through the implementation of the plan. In the life of an Islamic education organization which contains a collection of a number of people, there is a division of occupations. The division of work creates the existence of leaders and members, whose authority and role models influence members to work voluntarily and jointly achieve goals based on Islamic values.